2023
DOI: 10.1097/hep.0000000000000547
|View full text |Cite
|
Sign up to set email alerts
|

Host genetic variation guides hepacivirus clearance, chronicity, and liver fibrosis in mice

Abstract: Background & Aims: Human genetic variation is thought to guide the outcome of hepatitis C virus (HCV) infection but model systems within which to dissect these host genetic mechanisms are limited. Norway rat hepacivirus (NrHV), closely related to HCV, causes chronic liver infection in rats but causes acute self-limiting hepatitis in typical strains of laboratory mice, which resolves in two weeks. The Collaborative Cross (CC) is a robust mouse genetics resource comprised of a panel of recombinan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…CC strains have been a useful tool to relate genotype to phenotype in mice for many disease states, infectious and otherwise. For pathogenic human RNA viruses, CC strains have enabled understanding of host genetics impacting a variety of viruses, including SARS-CoV 31,32,33,34,35,36 , influenza virus 37,38,39,40,41,42 , Ebola virus 43,44 , West Nile virus 45,46,47,48 , Theiler's murine encephalitis virus 49,50,51,52,53 , lymphocytic choriomeningitis virus 54 , Zika virus 55 , SARS-CoV-2 17,36 , Rift Valley fever virus 56 , Powassan virus 57 , and recently, Norway rat hepacivirus 58 , which is closely related to HCV. These studies have revealed mouse genetic background impacts overall susceptibility to infection, viral burdens, host survival, levels of tissue inflammation, innate and adaptive immune responses, and differential gene expression after virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…CC strains have been a useful tool to relate genotype to phenotype in mice for many disease states, infectious and otherwise. For pathogenic human RNA viruses, CC strains have enabled understanding of host genetics impacting a variety of viruses, including SARS-CoV 31,32,33,34,35,36 , influenza virus 37,38,39,40,41,42 , Ebola virus 43,44 , West Nile virus 45,46,47,48 , Theiler's murine encephalitis virus 49,50,51,52,53 , lymphocytic choriomeningitis virus 54 , Zika virus 55 , SARS-CoV-2 17,36 , Rift Valley fever virus 56 , Powassan virus 57 , and recently, Norway rat hepacivirus 58 , which is closely related to HCV. These studies have revealed mouse genetic background impacts overall susceptibility to infection, viral burdens, host survival, levels of tissue inflammation, innate and adaptive immune responses, and differential gene expression after virus infection.…”
Section: Discussionmentioning
confidence: 99%